Pengembangan Modul Digital Interaktif Berbasis Website menggunakan Kerangka Kerja Borg, Gall, And Gall pada Mata Pelajaran Administrasi Sistem Jaringan di SMK Negeri 12 Malang - Iwan Majid; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Retrieval of data has the objective to carry out the development of interactive digital modules while on the basis of the website to enhance the process of achieving competency expertise and find out how feasible, efficient and effective the product is as supporting the learning process of VOC Network System Administration in the discussion of virtual private networks. The data collection method used is Research and Development using the Borg, Gall & Gall framework. The object in data collection is 12th grade SMK Negeri 12 Malang students 1. Based on the results of data retrieval, the validity of the material expert stated 3.47 (valid). The acquisition of validity of media experts stated 3.48 (valid). Obtaining the validity of the learning implementation plan stated 3.1 (valid enough). Obtaining validity about the pre-test post-test stated 3.58 (valid). The acquisition of student response questionnaire stated 3.27 (valid). To realize the increased achievement of knowledge competencies carried out while submitting pre-test and post-test. Through the calculated Z value and Z table, the results of the assessment on the virtual private network lessons calculated using the Wilcoxon Test obtained the calculated Z value as large as -4.10 and the Z value as large as 0.00001. The acquisition of Z count has a value smaller than the value of the Z table, so it can be stated that the acquisition of post test is better than the acquisition of pre test. The results obtained from the previous information, data collection shows that the development of interactive digital modules based on the website on virtual private network material is feasible, efficient and effective in the learning process and may be used as a learning process media in order to improve the achievement of students' knowledge competencies.